Maternal opioid use during pregnancy and the risk of neonatal opioid withdrawal syndrome in the offspring - Anna Warncke Kristensen; Vibeke Vestermark; Anette Kjærbye‐Thygesen; Maria‐Christina Eckhardt; Ulrik Schiøler Kesmodel (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction Neonatal opioid withdrawal syndrome (NOWS) is caused by sudden cessation from in utero exposure to opioids. The indications for opioid use during pregnancy are diverse including medication for opioid use disorder and analgesia. The opioid dose typically depends on the indication, with higher doses used for medication for opioid use disorder and lower doses used for analgesia. The aim of this study was to investigate the relationship between maternal opioid dose during pregnancy and the risk of NOWS. Material and Methods We conducted a historical multicenter cohort study of neonates prenatally exposed to opioids in Eastern Denmark during a six‐year period from 2013 to 2018. The data was extracted from reviewing the individual's medical record(s), which were identified through a search of the Danish National Patient Register. Four groups (quartiles) according to maternal opioid dose during the last four weeks prior to delivery were compared. Unadjusted and adjusted logistic regression analyses were conducted to examine the risk of NOWS while controlling for relevant covariates. Results A total of 130 in utero opioid exposed neonates were included. The majority of the pregnant patients (88%) were treated with opioids for analgesic purposes. Overall, 52% of neonates developed NOWS. The cumulative incidence of NOWS was 21%, 28%, 67% and 91% at maternal average daily dose of morphine milligram equivalent during the last four weeks prior to delivery of 0.7–14 (group I), 14.3–38.6 (group II), 40–90 (group III) and 90.9–1440 (group IV), respectively. Compared to group I the adjusted odds (aOR) of NOWS increased significantly in group III (aOR 10.6 [2.9–39.1]) and group IV (aOR 37.8 [7.6–188.2]) but not in group II (aOR 1.5 [0.4–5.2]). No cases of NOWS were reported at maternal dose less than an average daily dose of five morphine milligram equivalent during the last four weeks prior to delivery. No significant changes in the incidence of NOWS were observed between 2013 and 2018. Conclusions The odds of neonatal opioid withdrawal syndrome increased significantly as the maternal average daily dose of morphine milligram equivalent during the last four weeks prior to delivery surpassed 40.